Pemberdayaan Industri Kecil Dan Menengah Untuk Usaha Pertumbuhan Ekonomi Daerah - Istiasih, Hermin (Nusantara of Engineering, 2015)
Abstract: Target of which will reach inthis research is analyze there itsinfluence of size measure variable ofeffort, capital aid and way of processthe effort to growth of effort of bananain Countryside of Kediri City.Population in this research is all middleand small industrial organizer andentrepreneur